5x+12=6x-44

Simple and best practice solution for 5x+12=6x-44 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+12=6x-44 equation:



5x+12=6x-44
We move all terms to the left:
5x+12-(6x-44)=0
We get rid of parentheses
5x-6x+44+12=0
We add all the numbers together, and all the variables
-1x+56=0
We move all terms containing x to the left, all other terms to the right
-x=-56
x=-56/-1
x=+56

See similar equations:

| a=2*15 | | -9x=-10x+6 | | 3x-2(-7+13)=-196 | | -251=7(7n-5)+5n | | X^2-x-184=0 | | 5(3x-7)=-140 | | 3x+2(-6x+10)=-88 | | -3x–8=-11 | | -14=3(v+7)-8v | | 17x-14=3x+4 | | x-(.75)=20 | | p(30309)=28000(1.02)^30309 | | 8.2k+1.5=3.2k-0.9 | | 3*(1/3x-12)=7x+6 | | -4(-4x+2)=-13x-3 | | 16/g;g=4 | | 3(-x=1)+2=2(2x-4)-1 | | 7(m-6);m=8 | | 16x+7=4x-3 | | 3x+4x=x+60 | | 242=11(x-4) | | 10v-7v=15 | | -3(2y-4)=12-6y | | 2(3x+2)=2(2x-1) | | Y-3y+3y-y=0 | | 7m-6;m=8 | | 2.3+x/3=-2.5 | | 3x+(x/2)=42 | | (3*9)*8=98*3)*n | | 5/9=2/27y | | 3(1/3x-12)=7x+6 | | 2(4v-9=14 |

Equations solver categories